Analysis of a Cooperation and Interventional Model in Humanitarian Medicine - Marianeschi, Stefano M.; Uricchio, Nicola; Cerri, Gianandrea Bern; Ghiselli, Simone; Carro, Cristina; Albano, Giulia; Viola, Nicola (Frontiers in Pediatrics, 2021)
Background Every year, around 15 million children, in developing countries, die or develop life-long disabilities because of congenital cardiac diseases. In this report we measure the effect of a pediatric cardiac surgery humanitarian project on the health of the individual and on the potential influence this has on the countries economy and its growing health services. Methods We collected and analyzed data from the Italian NGO, Mission Bambini’s database, including all congenital cardiac missions undertaken in Cambodia between 2012 and 2019. DALY’s (Disability Adjusted Life Years) saved by the humanitarian mission were estimated and used to reflect on the impact this had on the populations economy. Progression in the local medical teams skills emulated the advancements made in the health sector of the region. Results Between 2012 and 2019, 128 patients underwent a congenital cardiac operation at Angkor Hospital for Children at Siem Reap, Cambodia. The median age was 6 years. The majority of the pathologies included VSD, TOF, ASD. The mean Aristotle’s Complexity Score was 6. Post-operative mortality was 0,8 % (1/128). The cost-effectiveness analysis identified 5.360 DALY’s saved by surgery. The competency of the local team was progressive with them being able to handle more complex cases on subsequent missions. Conclusion In developing Countries, performing congenital cardiac surgery cases can be carried out successfully with improvement in both the economy and the health system of the country by increasing the years and the quality of life of the working population and developing the expertise of the regional team.